PENGARUH KREATIVITAS GURU DAN LINGKUNGAN BELAJAR SEKOLAH TERHADAP HASIL BELAJAR SISWA DI SMA EKASAKTI PADANG - Fifi Affriyani; Salman M. Noer; Reni Respita (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Ekasakti, 2024)
The research results of the teacher's creativity variable have t count (9.488) > t table (2.0016) and the sig value of the calculation obtained is 0.000 <0.05. This means that H1 is accepted and Ho is rejected. So it can be concluded that teacher creativity has a significant effect on student learning outcomes at Ekasakti Padang High School. The learning environment variable has t count (4.970) > t table (2.0016) and the calculated sig value obtained is 0.000 <0.05. This means that H2 is accepted and Ho is rejected. So it can be concluded that the learning environment has a significant effect on student learning outcomes at Ekasakti Padang High School. The calculated F value is 157.735 which is greater than the F table value of 3.17 (see attachment table F) and the probability value resulting from the calculation is 0.000b less than α (5%). This means that H3 is accepted. Based on the test results it can be stated that it can be stated that teacher creativity and the learning environment together have a significant effect on student learning outcomes at Ekasakti Padang High School with a degree of success of 95% (α = 5%).